Planning the upstream agricultural landscape of the Jeneberang watershed using the bioregion approach. Issue 1 (April 2020) - Dariati, T; Firnawati,; Yanti, C W B; Dungga, N E; Iswoyo, H; Mantja, K; Zainuddin, D U
Abstract: This study aimed to plan the agricultural landscapes in the upstream area of the Jeneberang watershed using a bioregion approach. This research was conducted in the upstream area of the Jeneberang watershed precisely in the Pattapang Village, Tinggimoncong District, Gowa Regency, South Sulawesi from May to July 2017. The research was conducted using a field survey method and literature study, which included five stages, namely the preparation, inventory, analysis, synthesis and planning stages. The criteria for the classification of the bioregions were prepared based on the characterization of the biophysical and socio-cultural aspects of the Pattapang community based on the inventory, analysis and synthesis of the data obtained. At the planning stage, the conceptualization for landscape conservation is carried out, then the development of planning concepts and the end result is a sustainable agricultural landscape plan that can still meet economic needs. Based on the results of the bioregion analysis, the study area is included in the bioregion units of the Jeneberang watershed, namely the Jeneberang watershed upstream area, consisting of 70 sub-watershed units divided into 121 landscape units based on three biophysical characters (sub-watersheds, soil types and slopes) and 156 units a place based on the socio-cultural intrinsic value of land cover. The landscape plan for sustainable agriculture consists of 61.7 ha of residential space, agricultural area (35.4 ha of rice fields, 384.3 ha of monoculture fields and 780.94 ha of polyculture fields) and forests (89.6 ha of protected forests and 520.2 ha of production forest).